Teachers’ perspectives toward the implementation of bilingual immersion program in Indonesian private schools - Haris Ma'ruf; Huyi Intan Sari (Universitas Islam Sultan Agung, 2020)
This research was to find out teachers’ perspectives of the immersion program. For the mathematics, science and social subject teachers, it could ascertain how teachers cope with new challenges because using English to teach was a professional development experience and also could establish baseline approaches for implementing the immersion program. This study provided a picture of non-English teachers’ perception on implementing an immersion program at SMA Islam Sultan Agung 1 Semarang. The data was obtained from questionnaires and observation. The main challenge facing non-English language teachers was teaching and learning Mathematics, Sciences (Physics, Chemist, and Biology) and Social Subjects (Sociology, Economics, and Geography) in English. The study also showed that there were specific situations when teachers felt frustrated teaching an immersion class. This frustration always relates to lack of English language proficiency. In conclusion, this study shows the lack of English language proficiency is the main challenge faced by non-English language teachers and students in immersion classes at SMA Islam Sultan Agung 1 Semarang.